Protecting Law from Morality’s Stalking Horse: The ‘socio’ in much socio-legal studies - G. Wickham (Law Text Culture, 2008)
Invited a few years ago by one of the field’s leading journals ‘to stimulate discussion about the nature, role and future of socio-legal studies’ ( JLS Editors 2002: 632), Roger Cotterrell (2002) and Paddy Hillyard (2002), two leading socio-legal scholars, stress the connection between the legal and the moral. Morality, they believe, is the heart and soul of the law. For them, only when socio-legal studies allows the law-morality connection to be its guiding light is it at its strongest. To list five of their examples, this type of morality-to-the-fore socio-legal studies is open to many influences, is flexible in how it interprets these influences, produces a rich diversity of intellectual outcomes, expands the boundaries of what counts as ‘law’, and, in doing so, is a leader in the utilisation of the work of Michel Foucault (Cotterrell 2002: 632–9, Hillyard 2002: 646–50). The field would be lost, they suggest, without the law–morality connection. This high regard for morality — as the driving force of law, as the very raison d’être of socio-legal studies — is hardly unusual: it is the common currency of the highly influential brand of socio-legal scholarship that is consistent with the individual reason-based tradition (exemplified by John Rawls, esp. 1971) or the communitarian tradition (exemplified by Alisdair MacIntyre, esp. 1988). Yet I contend it is very dangerous, threatening the role of the law as a vital cog in modern Western countries.